Dual-specificity phosphatases in regulation of tumor-associated macrophage activity: review - Patysheva, Marina; Prostakishina, Elizaveta A.; Budnitskaya, Arina A.; Bragina, Olga D.; Kzhyshkowska, Julia (International journal of molecular sciences, 2023)
The regulation of protein kinases by dephosphorylation is a key mechanism that defines the activity of immune cells. A balanced process of the phosphorylation/dephosphorylation of key protein kinases by dual-specificity phosphatases is required for the realization of the antitumor immune response. The family of dual-specificity phosphatases is represented by several isoforms found in both resting and activated macrophages. The main substrate of dual-specificity phosphatases are three components of mitogen-activated kinase signaling cascades: the extracellular signal-regulated kinase ERK1/2, p38, and Janus kinase family. The results of the study of model tumor-associated macrophages supported the assumption of the crucial role of dual-specificity phosphatases in the formation and determination of the outcome of the immune response against tumor cells through the selective suppression of mitogen-activated kinase signaling cascades. Since mitogen-activated kinases mostly activate the production of pro-inflammatory mediators and the antitumor function of macrophages, the excess activity of dual-specificity phosphatases suppresses the ability of tumor-associated macrophages to activate the antitumor immune response. Nowadays, the fundamental research in tumor immunology is focused on the search for novel molecular targets to activate the antitumor immune response. However, to date, dual-specificity phosphatases received limited discussion as key targets of the immune system to activate the antitumor immune response. This review discusses the importance of dual-specificity phosphatases as key regulators of the tumor-associated macrophage function.
Gesehen am 16.04.2024